Bioconversion of agricultural waste into poly-γ-glutamic acid in solid-state bioreactors at different scales. (1st February 2020) - Fang, Junnan; Huan, ChenChen; Liu, Yang; Xu, Lishang; Yan, Zhiying
Graphical abstract: Highlights: Efficiently bioconversion of agricultural waste into γ-PGA of high-added value. First comparison of γ-PGA production in 50 L and 150 L solid-state bioreactors. Fermentation processes were upscaled from 10.00 kg to 37.50 kg of solid substrates. Initial analysis of the changes in solid substrates and bacterial communities. Abstract: With the purpose of developing a novel approach of agricultural waste treatment and overcoming bottlenecks for upscaling solid-state fermentation processes, the type of aerated, continuously stirred solid-state bioreactors were used for the production of γ-PGA by Bacillus amyloliquefaciens JX-6. Using corn stalk and soybean meal, the most common agricultural waste in China, as solid substrates, the maximum production of γ-PGA was 116.88 ± 5.05 g/kg and 102.48 ± 3.30 g/kg in 50 L and 150 L bioreactors, respectively. Production of γ-PGA in 50 L bioreactor was higher than in 150 L bioreactor, demonstrating that a reduction in γ-PGA production occurred as the fermentation system enlarged. An analysis of the interactions among fermentation parameters (temperature, moisture, and pH), γ-PGA production, solid substrates and bacterial communities indicated that different bioreactor capacities caused changes in fermentation parameters and bacterial communities, which in turn affected substrate utilization and γ-PGA production. Overall, obtaining considerable amounts of γ-PGA under non-sterilized fermentation expressed that JX-6 has excellent abilities to adapt to these substrates and conditions. Bioconversion of agricultural waste into γ-PGA in scale-up fermentation was successfully conducted by creating a more stable and suitable fermentation environment in bioreactors.